Auswirkungen einer Entkopplung von Ausgleichszahlungen auf den EU-Getreidemarkt - Horst Gom̈ann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Impacts of a Decoupling of Direct Payments on the EU Cereals Market: The proposals for reforming the Common Agricultural Policy within the Mid Term Review of the European Commission fueled the discussion about the future of direct payments to farmers. The EU Commission recommends a decoupling of animal and area payments from the production by granting these direct payments as a payment claim per hectare of eligible farm land. However, introducing area tied payments the intended shift of payments from the produce to the producer will not take place, but instead an increased transfer of payments to land owners seems likely. This study therefore analyses the impacts of changing the area payments for grand cultures into person-tied payments on the cereals market of the European Union. For the assessment of impacts homogenous natural locations are clustered. The clustering is based on the regional reference yields for cereals and the share of arable land of total agricultural area in different farm types of the regions. For these production locations total production costs for cereals, oilseeds, and protein crops are calculated as a function of the farm size in order to estimate a cost reduction potential subject to structural changes within agriculture. The main results are the following: 1) Prerequisites are good for the EU to cultivate cereals since a major part of the production is located in highly competitive regions. Thus the EU would remain a net exporter of cereals even producing under world market conditions. However, maintaining the intervention price system while abolishing the set-aside obligation could lead to an uncontrolled increase of cereal stocks. 2) Even on highly competitive locations a significant structural change is required in order to reduce costs and to yield profits without area payments. Depending on the development of the world market prices for cereals the model calculations find a reduction of the work force between 20 000 and 50 000 labor units.3) Without area payments the profits per hectare and thus the rents would decrease notably and therefore result in a corresponding income loss for land owners. An exclusive granting of payment claims to the producers would in particular affect former farmers, whose rental incomes contribute substantially to their pension plans.
Keywords: 330; Agrarsubvention; EU-Agrarpolitik; Getreidemarkt; EU-Staaten